Tasks in Technology: An analysis of their purposes and effects - Kimbell, Richard (Design and Technology Education: An International Journal, 2015)
Introduction for the 2015 DATA Special Edition This paper was written in 1993 and was published in The International Journal of Technology and Design Education. 1994 Springer 4(3): 241-256. The paper concerns the nature of the tasks that initiate and drive technological activity. It is set in the context of two research projects that we conducted in TERU; the Assessment of Performance Unit project in Design & Technology (1985 to 1991) and the Economic and Social Research Council project “Understanding Technological Approaches” (UTA) (1992-1994). The former was a large scale national survey of performance in schools - involving tests on 10,000 learners in 700 schools, and the latter is a small scale study (80 learners in 20 schools) examining in detail the processes that learners engage in as they tackle technological tasks. However, the wider context of this paper concerns the English and Welsh National Curriculum (NC) implementation programme that had been launched in 1990. It caused a huge storm both in the curriculum generally and in design & technology (d&t) in particular. In the wider curriculum the assessment arrangements surrounding the Standard Assessment Tasks had been so badly designed that in 1992 teachers and schools had boycotted the whole process. And in d&t, the ‘Order’ that defined what teachers should do in the classroom/studio/workshop appeared to make very different demands on teachers than had previously been the case. The Order defined d&t in four ‘Attainment Targets’, the first of which (AT1) was ‘Identifying Needs and Opportunities’. This (at least) implied that learners themselves should be doing that ‘identifying’, and in 1990 that was far from common practice. At exactly this moment we undertook the ESRC: UTA project that enabled us to collect the data that would inform this issue. We followed in detail the tasks that teachers set or negotiated with learners and examined the consequences of these tasks on ’ subsequent actions.